KARYA TARI GLADEN - Rahayu, Nanuk (Acintya, 2010)
The continuity of physical exercises is most required for the dancer who depends on their body as a tool and expression source. Phisycal exercises or known as â€œ injeksi â€œ is expected to make the body smart, responsive and has a performance power or the expression power in every single dance work.â€œInjeksiâ€ as a body exercise can give provisions to the dancer candidate student in order to have a good stamina and be ready to do all kinds of movements. Through these â€œ Injeksi â€œ activities, the choreographer wants to revitaling again the dance concepts which has been created by The late Gendhon Humardani. One of those concepts is simple dance concept which is manifested through the dance workâ€Female group and push forward on active, lively and quick movements, also gentle and glorious movementsâ€. The working of this dance work takes the one of Srikandi figure with all her problems that attitude is placed and reflected in a whole united work â€œGLADHENâ€ Keywords: gladhen, stamina, dancework